Implementasi Layanan Bimbingan dan Konseling di SMA Negeri 2 Telukjambe Timur - Rafif Agustian, Naufal; Harfi Mutmainah, Diva; Syabila Putri Maulana, Amanda; Fitri Zulkarnaen, Aninda; Aini Farida, Nur (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research examines the implementation of Guidance and Counseling services at SMAN 2 Telukjambe Timur through a descriptive lens. Employing a qualitative methodology, (Hazizah Isnaini, 2024)data were gathered via direct observations and semi-structured interviews involving guidance counselors and eleventh-grade students. The analysis focused on delineating service provision, counselor roles, and student perceptions of these functions within the educational setting. Findings reveal that services operate effectively on both scheduled and impromptu bases, integrating core activities such as basic support, responsive interventions, personalized counseling, and systemic backing. Participants reported significant value in the offerings, which include aptitude assessments and career development initiatives. Notwithstanding, challenges persist for both counselors and students. In aggregate, the program functions proficiently, bolstered by comprehensive school-wide collaboration.